(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The teacher shortage is an international problem, teacher job satisfaction merits closer attention. Not only is job satisfaction closely related to teacher retention, but it also contributes to the well-being of teachers and their students, overall school cohesion, and the enhanced status of the teaching profession. The goal of this research was to look at the link between work autonomy and job proficiency in instructors. The study also looked at the most important aspects of work proficiency. Two surveys on 100 teachers took part in the research, with 42 men and 58 women were used to collect data for this study in Delhi/NCR area private B-schools. Work autonomy is highly associated with job proficiency, according to the findings. It also revealed that respondents had a high degree of work proficiency and autonomy. Furthermore, money was reported to be the least satisfying feature among instructors in this study. The teachers’ experience, gender, work proficiencies, and job autonomy had no significant relationship. Finally, this research has instructive implications for the management who want to create a happy working environment for their teachers.